Higher versus lower enteral calorie delivery and gastrointestinal dysfunction in critical illness: A systematic review and meta-analysis. Issue 10 (October 2022) - Murthy, Tejaswini Arunachala; Plummer, Mark P.; Tan, Elinor; Chapman, Marianne J.; Chapple, Lee-anne S.
Summary: Background and aims: In critical illness, enteral nutrition (EN) is frequently limited by gastrointestinal (GI) dysfunction. The aim of this systematic review and meta-analysis was to determine relationships between enteral calorie delivery and GI dysfunction in critically ill adults. Methods: MEDLINE, EMCARE, EMBASE, and CINAHL databases were searched from 1 January 2000 to 11 August 2021 to identify parallel group randomised controlled trials of an EN intervention that resulted in a significant difference in calorie delivery between groups and reported at least one outcome relating to GI dysfunction. Study groups were categorised as 'higher' or 'lower' calorie delivery and data were extracted on study interventions, GI dysfunction and clinical outcomes. Extracted data were aggregated using a random effects model and presented as risk ratio with 95% confidence intervals. A P-value <0.05 was considered significant. The risk of publication bias was assessed graphically using a funnel plot. Results: From 13 studies involving 6824 patients the mean calorie delivery in the higher calorie group was 1673 ± 468 kcal/day compared to 1121 ± 312 kcal/day in the lower calorie group. The higher calorie group had an increased risk of a large (any volume ≥300 ml) gastric residual volume (GRV) (RR 1.40; 95% CI 1.09, 1.80; P = 0.009) and prokinetic administration (RR 1.18; 95% CI 1.11, 1.27; P < 0.00001). There were no between group differences in the presence of vomiting/regurgitation (RR 0.93; 95% CI 0.58, 1.49; P = 0.76), diarrhoea (RR 1.12; 95% CI 0.93, 1.35; P = 0.22) or abdominal distension (RR 0.71; 95% CI 0.49, 1.04; P = 0.08). There was no evidence of publication bias. Conclusion: Higher calorie delivery is associated with increased rates of GRV≥300 ml and prokinetic administration, but not vomiting/regurgitation, diarrhoea or abdominal distension. Other: No funding was received for the conduct of this systematic review and meta-analysis. The protocol was prospectively registered with PROSPERO (CRD42021268876).